Completeness of death registration in Ghana: An evaluation of multiple data sources and methods - Charles Agyei-Asabere; Ayaga Agula Bawah; Faustina Frempong-Ainguah; Jill Baumgartner; Samuel Agyei-Mensah; Emmanuel Botchway; Victor Sowah Abordo; Majid Ezzati (PLoS ONE, 2026)
Introduction The lack of a robust and comprehensive civil registration system undermines efforts to develop policies that address emerging health issues in a population. While Ghana has made significant strides in birth registration, progress in death registration has lagged despite the system’s introduction in 1888. Death records are dispersed across institutions and hampered by weak coordination and inconsistent data sharing. The study aims to evaluate the completeness of death registration using both demographic and empirical methods. Methods We assessed the quality of mortality data using demographic methods and further applied Death Distribution Methods (DDM) as well as the Empirical Completeness Method (ECM) to evaluate the completeness of death registration from the 2022 mortality register and two rounds of population and housing censuses. Findings Age reporting ranged between fairly accurate and rough, with noticeable under-reporting of under-five deaths. Death registration completeness was estimated at 28.7 percent and 56 percent using the ECM and DDM, respectively. DDM results reveal that male completeness was highest (101%) in the Volta Region and lowest (42%) in the Western Region, while female completeness was highest in Upper East (89%) and lowest in Western (35%) regions. Sub-national variations in completeness were further highlighted by the ECM, with completeness ranging from nearly 70 percent in Greater Accra to barely 8 percent in the Oti Region. Conclusions The study revealed that completeness of death registration remains low and incomplete, with minimal improvement over the past two decades. The findings underscore the urgent need to adopt innovative, targeted and coordinated approaches to improve completeness, ensuring Ghana can meet international commitments such as SDG 17.19.2.